A peroxiredoxin‐based proteinaceous scaffold for the growth and differentiation of neuronal cells and tumour stem cells in the absence of prodifferentiation agents. (8th February 2016) - Cimini, Annamaria; Ardini, Matteo; Gentile, Roberta; Giansanti, Francesco; Benedetti, Elisabetta; Cristiano, Loredana; Fidoamore, Alessia; Scotti, Stefano; Panella, Gloria; Angelucci, Francesco; Ippoliti, Rodolfo
Abstract: The use of nanoscale materials in the design of scaffolds for CNS tissue is increasing, due to their ability to promote cell adhesion, to mimic an extracellular matrix microenvironment and to interact with neuronal membranes. In this framework, one of the major challenges when using undifferentiated neural cells is how to control the differentiation process. Here we report the characterization of a scaffold based on the self‐assembled nanotubes of a mutant of the protein peroxiredoxin (from Schistosoma mansoni or Bos taurus ), which allows the growth and differentiation of a model neuronal cell line (SHSY5Y). The results obtained demonstrate that SHSY5Y cells grow without any sign of toxicity and develop a neuronal phenotype, as shown by the expression of neuronal differentiation markers, without the use of any differentiation supplement, even in the presence of serum. The prodifferentiation effect is demonstrated to be dependent on the formation of the protein nanotube, since a wild‐type (WT) form of the peroxiredoxin from Schistosoma mansoni does not induce any differentiation. The protein scaffold was also able to induce the spread of glioblastoma cancer stem cells growing in neurospheres and allowing the acquisition of a neuron‐like morphology, as well as of immature rat cortical neurons. This protein used here as coating agent may be suggested for the development of scaffolds for tissue regeneration or anti‐tumour devices. Copyright © 2016 John Wiley & Sons, Ltd.